ASP authentication using IP address / Kumar Mallanaidu - Kumar , Mallanaidu (2003)
The project undertaken is ASP Authentication Using IP Addressing; the mam objective of this project is to introduce the authentication technique for the websites, which are developed for any commercial organizations. This project just demonstrates the core key concepts of password authentication, data encryption. The project is developed using the Active Server Pages, which has the effective features to demonstrate and implement the authentication techniques. The technical concept of this project lies in providing security. There are many ways to implement the security concepts; one of the concepts we have chosen is the authentication technique using the IP (Internet Protocol) addressing. The main aim of this project is to implement the secured features for the users entering into a domain website. Here each aspect of the end user is controlled by the website server administrator. The logical reason is to control the user by giving them limited rights to access any entity or organization's information. Networking features behind this project plays an important role in identifying the end user location. Here the end user access to the server is monitored using the Internet Information Server, which supports the server side scripting effectively. The project is fully programmed using the server side scripting techniques, which forms a powerful basis for the web server to manage any number of users entering into the system.